Academic Planning Board Committee on Computer Requirements - Academic Planning Board Committee on Computer Requirements, PPSK (Universiti Pulau Pinang, 1971)
In preparing this report the Committee received support and cooperation from many organizations and individuals. Several computer companies, i,e, IBM, On-Line and ICL, provided useful technical information and participated in the Seminar on 'Computers and Their Applications', The Penang Port Commission and the Muda Agricultural Development Authority also participated in the Seminar. Eighteen government agencies and fifteen private firms responded to the mail questionnaire. Finally the Deans",the Registrar, the Bursar and the Librarian provided valuable information and criticism. To all these organizations and individuals the Committee would like to extend its sincere thanks.